2017
DOI: 10.1080/20008198.2017.1380471
|View full text |Cite
|
Sign up to set email alerts
|

Assessing therapeutic change in patients with severe dissociative disorders: the progress in treatment questionnaire, therapist and patient measures

Abstract: Background: Treatment research for dissociative identity disorder (DID) and closely related severe dissociative disorders (DD) is rare, and has been made more difficult by the lack of a reliable, valid measure for assessing treatment progress in these populations. Objective: This paper presents psychometric data for therapist and patient report measures developed to evaluate therapeutic progress and outcomes for individuals with DID and other DD: the Progress in Treatment Questionnaire – Therapist (PITQ-t; a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The Progress in Treatment Questionnaire, patient version (PITQ‐p; Schielke, Brand, & Marsic, ) is a self‐report measure that assesses ability to manage emotions, symptoms, relationships, safety, and well‐being over the prior 7 days. The PITQ‐p consists of 32 expert‐identified items, 6 of which (items 27–32) are only completed by patients who report experiencing dissociative self‐states (DSS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Progress in Treatment Questionnaire, patient version (PITQ‐p; Schielke, Brand, & Marsic, ) is a self‐report measure that assesses ability to manage emotions, symptoms, relationships, safety, and well‐being over the prior 7 days. The PITQ‐p consists of 32 expert‐identified items, 6 of which (items 27–32) are only completed by patients who report experiencing dissociative self‐states (DSS).…”
Section: Methodsmentioning
confidence: 99%
“…The Progress in Treatment Questionnaire, therapist version (PITQ‐t; Schielke et al., ) is a therapist‐completed measure of dissociative patients’ ability to manage emotions, symptoms, relationships, safety, and well‐being over the prior 6 months. The 29‐item instrument assesses the percentage of time patients have demonstrated expert‐identified adaptive behaviors and includes 6 items (items 24–29) that the therapist completes only for their patients with DSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in Treatment Questionnaire (PITQ). Finally, progress in treatment is determined using the Progress in Treatment Questionnaire, consisting of a part to be completed by the therapist (PITQ-t) and a part to be completed by the patient (PITQ-p) (Schielke, Brand, & Marsic, 2017). This questionnaire was specifically developed for treatment research in dissociative disorders and assesses (therapist ratings of) the patients' ability to safely and effectively manage their emotions, symptoms, and relationships.…”
Section: World Health Organization Disabilitymentioning
confidence: 99%
“…The sample may overlap with an article that shares authors and reports similar sampling methods (Jacobson et al, 2015). b Schielke et al (2017) reported that their study was part of the TOP DD study (Brand et al, 2009) but did not explicitly state that the sample overlaps with that study. c Studies were part of the TOP DD study (Brand et al, 2009) and only provided an estimated percentage of patients with DID.…”
Section: Identification Of Casesmentioning
confidence: 99%